Reconciliation of the Parties as a Way to Solve the Criminal-Legal Conflict - Степаненко, Оксана Василівна; Степаненко, О. В.; Степаненко, Оксана Васильевна; Stepanenko, Oksana V.; Степаненко, Андрій Сергійович; Степаненко, А. С.; Степаненко, Андрей Сергеевич; Stepanenko, Andrii S.; Stepanenko, Andriy; Ісраєлян, Алік Олександрович; Ісраєлян, А. О.; Исраелян, Алик Александрович; et al. (Editorial Primmate S. A. S., 2020)
The article explores the problem of resolving a criminal-legal conflict (which involves a person who has committed a socially dangerous act) through reconciliation. The relevance of the research topic is due to the fact that the legal conflict requires a binding solution, as it affects the most important social values. The purpose of this article is to disclose the nature and importance of reconciliation as a way of resolving a criminal-legal conflict. The authors used an analysis method, a synthesis method, a logical method, a historical method, and a formal legal method to write this article. According to the results of the study, the authors concluded that the application of criminal liability for reconciliation of the perpetrator with the victim is effective for all parties to the criminal-legal conflict. Moreover, for the state as a party to the criminal-legal conflict, such a way of resolving, is also effective because of the fact that the achievement of the tasks of criminal responsibility with the minimum cost of resources is the restoration of the rights of the victim.

Стаття досліджує проблему вирішення кримінально-правового конфлікту (в який вступає людина, що вчинила суспільно небезпечне діяння) шляхом примирення. Актуальність теми дослідження обумовлена тим, що кримінально-правовий конфлікт, потребує обов’язкового вирішення, оскільки зачіпає найбільш значущі суспільні цінності. Метою даної статті є розкриття сутності та значення примирення як способу вирішення кримінально-правового конфлікту. Автори використали метод аналізу, метод синтезу, логічний метод, історичний метод та формально-юридичний метод для написання даної статті. За результатами приведеного дослідження автори дійшли висновку, що застосування звільнення від кримінальної відповідальності у зв’язку з примирення винного з потерпілим є ефективним для всіх учасників кримінально-правового конфлікту. Більш того, для держави, як учасника кримінально-правого конфлікту, такий шлях його розв’язання є також ефективних в силу того, що відбувається досягнення завдань кримінальної відповідальності з мінімальними затратами ресурсів, відбувається відновлення прав потерпілого.
Stepanenko O. Reconciliation of the Parties as a Way to Solve the Criminal-Legal Conflict / O. Stepanenko, A. Stepanenko, A. Israielian // Amazonia Investiga. – Vol. 9. - Issue 28. – Editorial Primmate S. A. S., 2020. – P. ‏ 288-295.
Keywords: criminal-legal conflict; reconciliation of parties; criminal procedure; victim; conflict resolution; кримінально-правовий конфлікт; примирення сторін; кримінальний процес; потерпілий; вирішення конфлікту; Research Subject Categories::LAW/JURISPRUDENCE